LEAN AND SIX SIGMA IN MARITIME OPERATIONS: A TEN-YEAR SYSTEMATIC LITERATURE REVIEW - Hia, Selamat (Jurnal Ilmiah Teknik Industri, 2025)
This study presents a systematic review of Lean and Six Sigma (LSS) implementation in the maritime sector for the period 2016–2025, encompassing the contexts of ports, shipyards, logistics, the LNG industry, fisheries, and ship design. The analysis reveals a shift in focus from initial case studies to strategic implementation integrated with digital transformation, supply chain resilience, and sustainability. DMAIC and Value Stream Mapping methodologies dominate as the primary framework, supported by the integration of Industry 4.0 technologies and data analytics to maximize process efficiency. Quantitative evidence demonstrates the reduction in process time, reduction in defect rates, and significant operational cost savings. However, the success of LSS implementation is highly influenced by management support, human resource readiness, and the availability of reliable data, with the main obstacles being cultural resistance, limited initial investment, and lack of technical training. This study confirms that the future of LSS in the maritime sector is moving towards a hybrid model that combines Lean, Six Sigma, digitalization, and sustainability principles, which has the potential to become a global best practice in increasing the competitiveness of the maritime industry in an era of competition and uncertainty in the global supply chain.